Traumatic fibroma of orthodontic origin: a clinical case. - Landa Román, Cristóbal (2025)
Traumatic fibroma is a benign neoplasm that is triggered by the activation of platelet-derived growth factors (PDGF). These factors bind to specific receptors on the surface of fibroblasts, triggering the autophosphorylation of tyrosine residues and thus promoting the migration and proliferation of cells responsible for repair, such as fibroblasts. This injury arises mainly due to local, chronic or repetitive low-intensity traumatic factors, which can cause histological changes, such as pseudoepitheliomatous hyperplasia. The purpose of this work is to present a case of a traumatic fibroma derived from pausing and partially suspending dental consultations when wearing orthodontic appliances that are in contact with soft tissues. Demonstrating that in health emergency situations that lead to the closure of academic institutions where patients are treated, monitoring protocols must be implemented to avoid consequences of abandoning treatment. We present the case of a 34-year-old female patient seeking to resume her orthodontic treatment, which was interrupted due to the COVID-19 pandemic. The patient has a tumor on her cheeks associated with friction with the microimplants.